Efeitos da microinjeção intra vermis cerebelar de tioperamida na consolidação da memória emocional de camundongos - Costa Neto, Jorge (2013)
Experimental studies indicate that the cerebellum works not only in motor control but performs more complex tasks, such as the consolidation of emotional memory. The purpose of this study was to evaluate the effects of actions of thioperamide (THIO), histaminergic H3 receptor antagonist, in the consolidation of emotional memory in mice through the cerebellar vermis. To this was done two experiments. Experiment 1 used the elevated plus maze (EPM) as the test apparatus, and the experiment 2 used the Inhibitory Avoidance Test (IAT). In both experiments were utilized four experimental groups of male mice of Swiss Albino strain, weighing between 25-35g. All animals were submitted to surgical procedure that consisted in the implementation of the guide cannula in the cerebellar vermis. In each experiment there was one control group that was treated with saline (SAL), and three groups that received pharmacological treatment of THIO different concentrations: 0.06, 0.3 and 1.5 ng/0.1μl. The tests were done on two consecutive days (exposure and reexposure), and drug treatment occurred immediately after exposure. The data were analyzed using analysis of variance (ANOVA) of a track followed by the Duncan test (P <0.01). It was concluded that, in both experiments, the data of previous exposure groups pharmacological treatment did not differ significantly and were grouped in pool. In experiment 1 the reduction of exploration of the open arms on reexposure was considered indicative of learning and memory. The data of experiment 1 pointed out a deficit of emotional memory consolidation for the group with lower dose of THIO (0.06ng /0.1μl), because the data of this group showed no statistical difference in relation to the pool for the variables %OAE and %TAE. The other groups (0.3 and 1.5 ng/0.1 μl), had a reduction in exploratory activity. There was also a statistical difference between the groups of reexposure, being the smallest group of THIO, statistically different from SAL and the two groups of larger doses used in this study did not show this difference. None of the doses used THIO intervened in locomotor activity of the animals, because there was no difference in the variable EAE. In experiment 2 was indicative of learning and memory latency increase on reexposure. The latency increase was observed in groups SAL, 0.06 and 0.3ng/0,1 μl compared with the pool. There was no difference for the group 1.5 ng/0.1 μl. Among the group data of reexposure, there was a difference of 0.3 THIO groups and 1.5 ng/0.1 μl compared to the control, and this difference was not observed in group THIO 0.06.